Clinical Characteristics of Patients With Solitary Pulmonary Mass After Radical Treatment for Primary Cancers: Pulmonary Metastasis or Second Primary Lung Cancer?. (1st July 2013) - Ge, Jun; Gou, Hong-Feng; Chen, Ye; Cheng, Ke; Li, Long-Hao; Dong, Hang; Gao, Feng; Zhao, Feng; Men, Hai-Tao; Li, Qiu; Qiu, Meng; Su, Jing-Mei; et al.
<x xml:space="preserve">Abstract</x> We identified clinical characteristics of 30 pulmonary metastasis (PM) patients and 29 second primary lung cancer (SPLC) patients with feature of solitary pulmonary mass (SPM) after radical treatment of prior cancers. 6.7% and 44.8% patients presented with centrally located SPM and the median event-free durations were 33 and 72 months in PM and SPLC groups, respectively. PM was more likely to be found in prior cancers with stage III. In conclusion, the location of SPM, the event-free duration and the prior tumor staging were important features for differentiating SPLC from PM among patients with SPM after prior cancers.